The ecology of citizenship: understanding vulnerability in urban Brazil. Issue 1 (January 2017) - Coates, Robert; Garmany, Jeff
Abstract : This article calls into question the relationship between citizenship, space and ecological stability. Drawing on case study research from urban Brazil, we argue that while space may be crucial to Western perspectives of citizenship – particularly in urban areas – the ecological coproduction of these very same spaces is regularly overlooked. By not accounting for these processes, citizenship's promises continually fall short: though greater access to citizenship and its attenuating spaces may help to reduce one set of vulnerabilities (e.g. hunger, healthcare, informal housing), such change can further embed and even produce additional vulnerabilities for urban residents (e.g. disaster risk, environmental change, eviction). Thus citizenship, in Brazil as well as elsewhere in the world, remains a morose relationship between people and the state, where promises of security and sustainability can never be fully realised. Such bleak outcomes are inevitable, we argue, so long as the coproductive/destructive links between environmental processes and citizenship are ignored, and expectations of citizenship fail to account for broader spatial and ecological contexts.